Enhancing wastewater treatment with engineered biochar from microwave-assisted approach - A comprehensive review - Foong, Shin Ying; Bridgid Chin, Lai Fui; Serene Lock, Sow Mun; Yiin, Chung Loong; Tan, Yie Hua; Guiyang, Zheng; Shengbo, Ge; Rock Keey, Liew; Lam, Su Shiung (Elsevier B.V., 2024)
The growing global concern over water pollution has urgently demanded cost-effective and highly efficient methods and materials for removing pollutants. Biochar is a promising material for use as an adsorbent due to its abundance, low cost, porous surface, and alterable surface functional group. This review provides a detailed insight into the current state-of-art of biochar production from microwave-assisted pyrolysis, activation approaches to improve the physicochemical properties of biochar, and the applications of biochar in various pollutants from wastewater, including heavy metals, dyes, antibiotics and nutrients from aquaculture. Pyrolysis is a promising method for producing biochar, but the drawbacks of conventional pyrolysis are slow processing and low energy efficiency. Microwave-assisted pyrolysis has undergone extensive study due to its distinctive heating mechanism, which facilitates rapid feedstock heating, thereby enhancing energy efficiency and yielding pyrolytic products of improved quality and quantity. The biochar produced has a high surface area (up to 1500 m2/g) and exhibits different functional groups that are effective for pollutant adsorption from wastewater. Methods for activating biochar based on physical activation with assistance from microwave heating can offer a cost-effective and straightforward approach to producing engineered biochar for large-scale wastewater treatment. Conversely, chemical activation can provide specific surface functional groups tailored to meet requirements for removing pollutants. However, further research is necessary to optimize the production of engineered biochar, enhance its adsorption properties, and develop efficient regeneration techniques for its widespread application in large-scale wastewater treatment systems.